Reconciling Indigenous peoples with the judicial process: An examination of the recent genocide and sexual slavery trials in Guatemala and their integration of Mayan culture and customs - Patterson, Elisabeth (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2016)
This article examines two recent landmark cases in Guatemala. The first one is the 2013 Rios Montt genocide case, which led to one of the first convictions of a former Head of State for genocide in a national court. The second one is the 2016 Sepur Zarco case, which marked the first time former military commanders were convicted in a national court of crimes against the duties of humanity for sexual and domestic slavery. In both cases, almost all the victims were Indigenous. The author was present for parts of both trials as an international observer and interviewed individuals directly involved in the prosecution. Considering that Guatemalan and international law require that legal decisions give due consideration to the customs of the Indigenous peoples concerned, the article assesses to what extent Indigenous culture was taken into account during the trial and how Indigenous concepts and customs were considered in the judgements. In both cases, the tribunal did not modify usual court procedures, except to provide interpreters for the testimony of the unilingual Q’eqchi and Ixil witnesses. Both judgements did, however, take into account several concepts and customs from the Mayan worldview and these were key to the Court’s reasoning leading to the guilty verdicts.